Revisiting the Impact of Tungsten on the Catalytic Properties of Ammonia-SCR V2O5-WO3/TiO2 Catalysts: Geometric vs. Electronic Effects - Hermann Wilfried Siaka; Christophe Dujardin; Alain Moissette; Pascal Granger (Chemistry, 2023)
The SCR performance of V2O5-WO3/TiO2 SCR-catalysts characterized by different surface W density (2.1W/nm2 and 9.5W/nm2) and different surface V density varying in the range 1–8V/nm2 has been investigated in order to clarify existing controversies on the preferential involvement of electronic and geometric effects in the catalytic properties. It was found that tungsten has a weak effect on the VOx cluster size distribution through contraction of dilution effect. In contrast, the optimal interaction between W and V, when both reach their highest composition, appears to be a relevant parameter that can enhance their acidic properties and improve the catalytic efficiency in dry conditions. On the other hand, an absence of significant interaction leads to discontinuity due to deactivation. In the presence of steam, acidic properties are averaged, lowering the impact of the V to W ratio. Finally, the critical importance of acidic properties which outperform redox properties in the definition of active site is pointed out in the light of this study.